Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) Ikatan Makanan Olahan (IMO) dalam upaya legalitas usaha - Heri Kusmanto; Warjio Warjio; Evi Yunita Kurniaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Micro, Small and Medium Enterprises (MSMEs) are one of the entities of economic actors whose existence dominates the nation's economy, both in urban and rural areas, including businesses engaged in the culinary sector. In community service, it will empower the MSME Processed Food Association (IMO). Small business actors are advised to join the Processed Food/Beverage Association (IMO), with the aim of identifying all food/beverage businesses, which will then be easy to coordinate to accommodate the aspirations of SMEs such as knowing human resources, equipment, product quality or marketing accordingly with standardization criteria. Meet standardization, including to complete business legality. Small business actors who are members of IMO face various problems in terms of licensing and business legalization. Having a business license for the community is very important, but sometimes not a few people who do not want to take care of their business licenses due to lack of knowledge, limited data, and others. Through this service activity, the goals and targets to be achieved in the service activities are the legalization of business for business actors within the Processed Food Association (IMO). By having business legality, business people who are members of the IMO are expected to be able to compete in the free-market era. The method used in this service activity is carried out in the form of counselling, training and assistance in managing business legality.